Prevalence of soil-transmitted helminths in remote villages in East Kwaio, Solomon Islands - Harrington, Humpress; Bradbury, Richard; Taeka, James; Asugeni, James; Asugeni, Vunivesi; Igeni, Tony; Gwala, John; Newton, Lawrence; Fa`anuabae, Chillion Evan; Kilivisi, Fawcett Laurence; Esau, Dorothy; Flores, Angelica; et al. (Western Pacific Surveillance and Response, 2015)
Objective: Although soil-transmitted helminths (STH) are endemic in Solomon Islands, there are few recent reports on their prevalence. This study aimed to determine the prevalence of STH in residents of remote communities in Solomon Islands.Methods: A cross-sectional convenience-sampled survey of residents of four adjacent villages in Malaita, Solomon Islands was performed in Atoifi and Na’au in April 2011 and in Abitona and Sifilo in April 2012. All residents older than one year were invited to participate, which involved providing a single sample of faeces examined using a modified Kato-Katz technique and completing a questionnaire that asked demographic and STH-related behaviour questions.Results: The overall participation rate was 52.8%, with 402 participants comprising 49.8% males. Hookworm was the predominant STH with only a single case of trichuriasis found in Atoifi. The total prevalence of hookworm was 22.6% (95% confidence interval: 18.6–27.1); the prevalence of hookworm in Abitona, Na’au and Sifilo was 20.0%, 29.9% and 27.4%, respectively, whereas in Atoifi it was 2.3% (P